Odpowiedź :
f) (-5,5)×(-3 5/11)= 19
g) (-2 2/9)+4,6= 2 17/45
h) -1/2×2 1/4= -1 1/8
i) -1,8×(-5,6)= 10,08
j) (-6)²:(1+2³)= (-6×-6):(1+(2×2×2))= 36:9= 4
k) [(-3)²+2³]×(-5)= [(-3×-3)+(2×2×2)]×(-5)= [9+8]×(-5)= 17×(-5)= -85
Odpowiedź:
F (-5 5/10)*(-3 5/11)= - 5 1/2 * 38/11 = 11/2 * 38/11 = 38/2 = 19
G - 2 2/9 + 4 6/10= -2 2/9 + 4 3/5 = - 2 10/45 + 4 27/45 = 2 17/45
h = 0,5 * 2,75 = 13,75
I - 1 8/10 * (- 5/6) = - 18/10 * (- 5/6)= 3/2
J 36 : (1+ 8)= 36 : 9= 4
k ( 9 + 8)* (-5) = 17 * (-5) = -85
Szczegółowe wyjaśnienie: